Вивчення процесів ущільнення прес-порошків з високою вологістю - Хоменко, О. С.; Миршавка, О. О.; Васьковський, Р. К.; Михальска, Л. В.; Палагут, В. В. (НТУ "ХПІ", 2014)
В роботі приведено дослідження процесів ущільнення прес-порошків з високою вологістю, які застосовуються при виробництві низьковольтних електротехнічних виробів складної конфігурації. Встановлено причини виникнення у виробах деформацій та розтріскування, викликаних нерівномірною усадкою відпресованого напівфабрикату. Пропонуються шляхи зниження негативного впливу усадочних процесів.

The paper presents the research process seal molding powders with high humidity, which are used in the manufacture of low-voltage electrical products of complex configuration. The causes of a product deformations and cracking caused by uneven shrinkage of the molded semi. Suggests ways to reduce the negative impact of shrinkage processes. In particular, to improve the sliding of the particles during compression, and their uniform distribution throughout the volume of the mold is recommended to use fatty component – oleic acid. Its most optimum amount of 0,8 %. At this stage you can mold provides a denser cake mix, which in turn contributes to the intensification of the sintering products.
The study condensation process press-powders with high moisture
Keywords: електрофарфор; тонкий помел; усадка; деформація; випал; electrical porcelain; fine grinding; shrinkage; deformation; burning